Danseurs wayãpi au Festival d’Avignon. Un spectacle interculturel, un acte diplomatique - Jean-Michel Beaudet (Centre de Recherches sur les Mondes Américains, 2017)
In 1987 ten dancers from the middle and upper Oyapock River in French Guyana were invited to attend the Festival of Avignon. What meanings did they ascribe to their journey? What did they expect from the spectacle? Through a description of the concrete conditions of the journey I approach these questions and contribute to the general discussion of intercultural spectacle. In fact, this invitation responded to a desire on the part of the dancers to know France and to become known there. To dance at the prestigious international festival of Avignon would have appeared to them as the best possible context for a group of important wayãpi men to make their first visit to France. For these dancers this spectacle was foremost an intercultural political act, an act of diplomacy.